PENGARUH KANDUNGAN SENYAWA BIOAKTIF EKSTRAK DAUN ANGSANA (Pterocarpus indicus) SEBAGAI INSEKTISIDA NABATI TERHADAP LARVA NYAMUK Aedes aegypti (L.) VEKTOR DENGUE DI BANJARMASIN - Risma Alaika Syafitri; Sevia Audia Martha; Nazula Ismaniar; Ananda Puteri; Muhammad Muslim; Risnawati Risnawati (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Control of dengue hemorrhagic fever (DHF) mosquitoes is generally carried out using synthetic pesticides. The use of synthetic pesticides is considered effective, practical, efficacious and economically more profitable. However, the use of synthetic pesticides continuously and repeatedly can cause environmental pollution, death of various types of living things and resistance from eradicated pests. One alternative that can be used to overcome the above problems is the use of natural insecticides (c), namely the Angsana plant (Pterocarpus indicus). This study aims to determine the effect of the compounds contained in the extract of the leaves of Angsana (Pterocarpus indicus), so the GCMS (Gas Chromatography Mass Spectrometry) test was carried out. The samples in this study were Aedes aegypti mosquito larvae in which each treatment group consisted of 25 larvae. Based on the results of the study it was found that there was an effect of the bioactive compound content of Angsana leaf extract (Pterocarpus indicus) as a vegetable insecticide on the larvae of the Aedes aegypti (L.) mosquito vector of dengue in the Banjarmasin region using ethyl acetate as a solvent at a concentration of 0.25%, 0.5 %, and 1%. While the most efficient concentration is 0.5% because it can kill Aedes aegyti larvae. Then based on the GCMS analysis results of the ethyl extract of Angsana leaves (Pterocarpus indicus) showed several compounds that have the potential as bioactive larvicidal compounds, namely Palmic Acid, Palmitate, Araldite 502, and Lupenone